(untitled) (Bangladesh Journal of Botany, 2023)
Grain yield and water use efficiency of wheat cultivars in relation to different sowing environments were evaluated where seven dates of sowing viz. October 22, 29, November 5, 12, 19, 26 and December 3 in the main plots and three varieties namely PBW 725, HD 3086 and HD 2967 in sub-plots’for three consecutive years were considered. Results revealed that wheat crop sown from October 22 to November 5 had better agrometeorological indices, yield attributes, normalized difference vegetative index and higher water use efficiency resulting in higher grain yield than delayed sowing. Wheat varieties PBW 725 and HD 3086 resulted the lower canopy temperature, higher grain yield along with all the yield attributing characters and agrometeorological indices under Northwestern conditions of India. Bangladesh J. Bot. 52(3): 701-707, 2023 (September)